To solve the system of equations:
- \( 3x - 4y = 40 \) (Equation 1)
- \( 5x - 5y = 55 \) (Equation 2)
First, we can simplify Equation 2:
\[ 5x - 5y = 55 \implies x - y = 11 \implies x = y + 11 \quad \text{(Equation 3)} \]
Now, we can substitute Equation 3 into Equation 1:
\[ 3(y + 11) - 4y = 40 \]
Distributing \(3\):
\[ 3y + 33 - 4y = 40 \]
Now combine like terms:
\[ -1y + 33 = 40 \]
Subtract 33 from both sides:
\[ -1y = 7 \implies y = -7 \]
Now we can substitute \(y\) back into Equation 3 to find \(x\):
\[ x = -7 + 11 = 4 \]
The solution to the system of equations is:
\[ (x, y) = (4, -7) \]
So the answer is \((4, -7)\).